(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
We present Gilbert Ryle’s analysis (1949/2009) of the logical operation of concepts related to emotions, including feelings, inclinations, agitations and moods. Ryle does not propose a new theory of emotions, but an analysis of how these concepts work in their “original home”, which is ordinary language. Through this guided reading of Ryle analysis, we seek to offer a concrete example and undo frequent confusion about the role of this kind of conceptual clarification, by showing that it is a prerequisite for establishing the conditions of sense of empirical questions. Before becoming part of psychological theories, emotion concepts are born and transformed in the contexts of human interaction which establish criteria for their use. When we forget this, we risk inadvertently revising concepts which may lead to confusion in theorizing and research questions that cannot logically be answered empirically.